2018
DOI: 10.1093/protein/gzy001
|View full text |Cite
|
Sign up to set email alerts
|

Development of novel metabolite-responsive transcription factors via transposon-mediated protein fusion

Abstract: Naturally evolved metabolite-responsive biosensors enable applications in metabolic engineering, ranging from screening large genetic libraries to dynamically regulating biosynthetic pathways. However, there are many metabolites for which a natural biosensor does not exist. To address this need, we developed a general method for converting metabolite-binding proteins into metabolite-responsive transcription factors-Biosensor Engineering by Random Domain Insertion (BERDI). This approach takes advantage of an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 40 publications
1
28
0
Order By: Relevance
“…Biosensor engineering by random domain insertion (BERDI) is another technique that can be used to generate new metabolite-responsive TFs. In this case, in vitro transposon-mediated mutagenesis was used to construct a TF library, followed by fluorescence-activated cell sorting (FACS) to isolate functional biosensors (Younger et al, 2017). Recently, MphR was found to bind promiscuously to macrolides, and was then engineered to improve its sensitivity, specificity, and selectivity for these small molecules (Kasey et al, 2017).…”
Section: Monitoring Metabolites In Vivomentioning
confidence: 99%
“…Biosensor engineering by random domain insertion (BERDI) is another technique that can be used to generate new metabolite-responsive TFs. In this case, in vitro transposon-mediated mutagenesis was used to construct a TF library, followed by fluorescence-activated cell sorting (FACS) to isolate functional biosensors (Younger et al, 2017). Recently, MphR was found to bind promiscuously to macrolides, and was then engineered to improve its sensitivity, specificity, and selectivity for these small molecules (Kasey et al, 2017).…”
Section: Monitoring Metabolites In Vivomentioning
confidence: 99%
“…The authors demonstrated the design of a maltose-responsive transcriptional biosensor based on the zinc-finger DNA-binding domain. 54 By employing the P sal promoter and SalR regulation system originally from A. baylyi ADP1, an inducible system responding to aspirin was developed. Without effector binding, the SalR was also capable of binding to the promoter to repress the transcription.…”
Section: Application Of Engineered Tfs Constructing Inducible Expressmentioning
confidence: 99%
“…Fortunately, there is a wealth of literature containing numerous case studies (recently reviewed in Bolbat and Schultz, 2017; Sanford and Palmer, 2017), because of early work on engineering of direct biosensors and protein switches (Siegel and Isacoff, 1997;Doi and Yanagawa, 1999;Prehoda et al, 2000;Tucker and Fields, 2001;Dueber et al, 2003;Guntas and Ostermeier, 2004). Ideally the design space of structurally reasonable fusions is thoroughly explored using protein engineering techniques to vary insertional position, linker residues between the modalities, and possibly circular permutation of one or both modalities (Kanwar et al, 2013;Younger et al, 2018). Recently, advances in bioinformatics and decreasing costs of next-generation sequencing have facilitated prediction and experimental determination of sites of potential allosteric regulation (Nadler et al, 2016;Rivoire et al, 2016;Pincus et al, 2017).…”
Section: Designmentioning
confidence: 99%
“…Transcription factors are an interesting alternative for connecting input and output modalities of direct or indirect biosensors, by allowing recognition of the species of interest to drive expression of any of the above output domains or another genetic circuit (Feng et al, 2015;Khakhar et al, 2016Khakhar et al, , 2018Younger et al, 2016Younger et al, , 2018. The amplification provided by transcription and translation may result in a wider dynamic range.…”
Section: Designmentioning
confidence: 99%